Comparison of Elecsys and Liaison immunoassays to determine Epstein–Barr virus serological status using further diagnostic approaches to clarify discrepant results - Lupo, Julien; Tsougaev, Mansour; Blachier, Stéphane; Chovelon, Guillaume; Truffot, Aurélie; Leroy, Corentin; Giai, Joris; Epaulard, Olivier; Germi, Raphaële; Morand, Patrice (Journal of medical virology, 2023)
Serological markers for Epstein–Barr virus (EBV) infection are commonly used to diagnose infectious mononucleosis and establish a serological status in pretransplant patients. This study prospectively assessed 1043 serum specimens sent to the laboratory for physician‐ordered EBV testing. The three markers—antiviral capsid antigen (VCA) immunoglobulin M (IgM), anti‐VCA immunoglobulin G (IgG), and anti‐Epstein–Barr nuclear antigen (EBNA) antibodies—were tested using the Elecsys and the Liaison immunoassays. Specimens with discrepant results between the two assays were assessed using further EBV diagnostic approaches to conclude on the EBV serological status. In spite of substantial agreement between the two assays (88%) and with the presumed EBV status (>92%), the results showed differences in the performance of the assays. Liaison VCA IgM appeared to be the most sensitive test for the detection of the 38 sera classified as early primary infection in comparison with the Elecsys assay (91.4% vs. 68.6%, p = 0.008). Excluding the cases of early primary infection, the sensitivity values of the VCA IgM marker were comparable between the Liaison and Elecsys assays (95.2% and 92.9%, respectively, p = 1). Concerning the sera classified as past infection (n = 763), the Elecsys assay showed higher sensitivity values for the detection of the VCA and EBNA IgG markers in comparison with the Liaison assay (99.9% and 99.7% vs. 97.4% and 91.2%, respectively, p < 0.001). Overall, the Elecsys and Liaison assays showed similar performance. The interpretation of EBV serological profiles based on the clinical context may require serology follow up or further diagnostic approaches in challenging cases.